ANALISIS YURIDIS PEMUNGUTAN PAJAK PERTAMBAHAN NILAI DALAM TRANSAKSI PERDAGANGAN MELALUI SISTEM ELEKTRONIK (PERATURAN MENTERI KEUANGAN NOMOR 60/PMK.03/2022) - Besdy, Besdy; Sahputra, Rilawadi; Azmi, Syariful (Smart Education, 2025)
Abstract: The digital economic transformation accelerated by the Covid-19 pandemic prompted the Indonesian government to implement tax policies on cross-border digital transactions. This study aims to evaluate the effectiveness of Value Added Tax (VAT) collection on intangible goods and/or taxable services from outside the customs area through Electronic-Based Trade (PMSE), and to assess its alignment with OECD guidelines. The research employs a normative juridical method with a descriptive qualitative approach, using literature review and interviews as data sources. The findings show a significant increase in the number of VAT collectors, from 51 entities in 2020 to 199 in 2024, with tax revenue rising from IDR 731.4 billion to IDR 8,440 billion. Supervision by the Directorate General of Taxes (DGT), supported by data from the Ministry of Communication and Information (Kominfo) and Bank Indonesia, is considered effective despite communication and transaction measurement challenges. The study confirms the effectiveness of the VAT collection policy for PMSE and its relevance in the digital economy context. Strengthening inter-agency coordination and developing more adaptive and comprehensive tax policies are recommended to enhance digital tax governance in Indonesia.Keyword: Digital Economy, Tax Compliance, Tax Supervision, VAT on E-CommerceAbstrak: Transformasi ekonomi digital yang dipercepat oleh pandemi Covid-19 mendorong Pemerintah Indonesia untuk menerapkan kebijakan perpajakan atas transaksi digital lintas batas. Penelitian ini bertujuan mengevaluasi efektivitas pemungutan Pajak Pertambahan Nilai (PPN) atas barang tidak berwujud dan/atau jasa kena pajak dari luar daerah pabean melalui Perdagangan Melalui Sistem Elektronik (PMSE), serta menilai kesesuaiannya dengan pedoman OECD. Kajian dilakukan menggunakan metode yuridis normatif dengan pendekatan kualitatif deskriptif, melalui studi kepustakaan dan wawancara. Hasil menunjukkan bahwa jumlah pemungut PPN PMSE meningkat dari 51 entitas pada 2020 menjadi 199 pada 2024, dengan penerimaan pajak naik dari Rp731,4 miliar menjadi Rp8.440 miliar. Pengawasan oleh Direktorat Jenderal Pajak (DJP), yang didukung data dari Kominfo dan Bank Indonesia, dinilai cukup efektif meski masih menghadapi kendala komunikasi dan pengukuran transaksi digital. Penelitian ini mengonfirmasi efektivitas kebijakan penunjukan pemungut PPN PMSE dan relevansinya dalam konteks ekonomi digital. Diperlukan peningkatan koordinasi antarlembaga serta pengembangan kebijakan yang lebih adaptif dan komprehensif untuk memperkuat tata kelola perpajakan digital di Indonesia.Kata kunci: Ekonomi Digital, Kepatuhan Perpajakan, Pengawasan Perpajakan, PPN PMSE